Estrategias prenatales para prevenir la muerte fetal en gestantes de riesgo. - Ayala Moreno, Peter Steeven; Paladines Loayza, Stefany Fernanda (My University, 2024)
Introduction: Fetal death is the absence of fetal heartbeat after 20 weeks of gestation, affecting approximately two million families annually, with emotional, social and economic implications. Objective: To establish prenatal strategies to prevent fetal death in pregnant women at risk. Methodology: A bibliographic review was carried out from November 2023 to March 2024, in different digital data sources. The search engine: Google Scholar and databases (PubMed, Fronteirs, Women and Birth) were used for the research with the help of the terms (fetal death, fetal movement, prevention, classification, risk factors, congenital syphilis, prenatal controls, clinical audits and infant mortality). Results: The initial search identified 5278 publications. Five duplicate publications and 5231 were filtered out after reading titles. Forty-five full-text articles were reviewed and 30 were excluded because they did not meet the inclusion criteria. Finally 10 studies were included and 5 were identified in the review, concluding in a total of 15 articles. Conclusion: Nutritional supplements, improvement of lifestyle habits, prevention of infections, sexual and reproductive health education for both spouses, training of midwives, application of audits, as well as follow-up of fetal wellbeing, improve the quality of prenatal care. In addition, the implementation of intervention plans that include these strategies can reduce the gap between prevention and fetal death.
Introducción: La muerte fetal es la ausencia de latidos cardíacos fetales después de las 20 semanas de gestación, que afecta aproximadamente a dos millones de familias anualmente, con implicaciones emocionales, sociales y económicas. Objetivo: Establecer las estrategias prenatales para prevenir la muerte fetal en gestantes de riesgo. Metodología: Se realizó una revisión bibliográfica en el periodo de noviembre-2023 hasta marzo-2024, en diferentes fuentes de datos digitales. Para la investigación se utilizaron el motor de búsqueda: Google Académico y bases de datos (PubMed, Fronteirs, Women and Birth) con ayuda de los términos (muerte fetal, movimiento fetal, prevención, clasificación, factores de riesgo, sífilis congénita, controles prenatales, auditorias clínicas y mortalidad infantil). Resultados: La búsqueda inicial identificó 5278 publicaciones. Se filtraron 5 publicaciones duplicadas y 5231 tras leer títulos. Se revisaron 45 artículos a texto completo y se excluyeron 30, por no cumplir con los criterios de inclusión. Finalmente 10 estudios fueron incluidos y 5 fueron identificados en la revisión, concluyendo en un total de 15 artículos. Conclusión: Los suplementos nutricionales, la mejora de los hábitos de vida, la prevención de infecciones, la educación en salud sexual y reproductiva en ambos conyugues, la capacitación a parteras, aplicación de auditorías, así como el seguimiento del bienestar fetal, permiten mejorar la calidad de los controles prenatales. Además, la implementación de planes de intervención que incluyan estas estrategias, puede disminuir la brecha entre la prevención y la muerte fetal.
Keywords: ESTRATEGIAS; MUERTE FETAL; FACTORES DE RIESGO; ATENCION PRENATAL